Students' Learning Difficulties In Understanding The Concept Of Multiplication And Root Form In Terms Of Students' Learning Styles - Asriani, Novita; Kadir; Samparadja, Hafiludin (Jurnal Amal Pendidikan, 2024)
This research is a qualitative descriptive study, and the purpose of this research is to determine which learning style is most effective in understanding the concepts of exponentiation and roots. The subjects of this research are 3 ninth-grade junior high school students, consisting of 1 student with a visual learning style, 1 student with an auditory learning style, and 1 student with a kinesthetic learning style. Data collected through questionnaires, essay tests, and interviews. The analysis techniques in this study are data condensation, data presentation, and conclusion verification. The results of this study indicate that students still have difficulty understanding the concepts of exponents and roots, and are unable to solve problems involving exponents and roots. Students with a visual learning style are able to write down information from the questions but struggle to grasp information conveyed verbally. Students with an auditory learning style can absorb information well through listening and direct written forms, but have difficulty in asking and communicating questions. Students with a kinesthetic learning style have difficulty understanding a problem, especially if it is verbal, and need to see the problem being discussed in its original form